SOSIALISASI TENTANG ASI EKSLUSIF DAN PRAKTEK PEMBUATAN MP-ASI DI WILAYAH KERJA PUSKESMAS GAMBESI - Ishak, Sitti Nurhidayanti; Buamona, Febrianti; Tutu, Gloria E.; Arsdiana, Nurul; Umalekhoa, Nilasari; Kahar, Julianti A.; Bandang, Jumaida; Dewi, Masthura Cita; S, Nissa Ariska; Malik, Sumarni; Ikmal, Linda; Piga, Radhiyah Rahma; Rahmawati, Nining; Silayar, Fika; Gorontalo, Rukmana; Jamaludin, Rahmat; Novarina, Yulia Yogi; Punusingon, Farhana; Nurintani, Nurintani; Sahbudin, Yulyana; Umaternate, Karmila; Umagapit, Rastiana; Rusman, Farida (LPPM Institut Pendidikan Nusantara Global, 2024)
ASI (breast milk) and MP-ASI (complementary foods for breast milk) have an important role in the development and health of babies. These two types of feeding play a crucial role in providing the nutrients needed for optimal growth and development of children. Unfortunately, there are still many mothers who do not provide exclusive breast milk, and what is even more worrying is that they give additional food when the baby is 4 months old. The team's efforts include outreach/counseling about the benefits of breast milk and MP-ASI. This activity aims to increase public knowledge about the importance of exclusive breastfeeding and continue providing appropriate MP-ASI. The method used was lectures through health outreach and direct practice targeting 20 people in Fitu village. The stages are preparation, implementation, and evaluation using a questionnaire. The results obtained were that after being given socialization about breast milk and the practice of making MP-ASI, it could be seen that there was an increase in participants' knowledge about breast milk and its various benefits. The public can find out how to make MP-ASI by themself. With this outreach, it is hoped that the community, especially mothers, would pay more attention to nutrition for children's growth and development, one of which is by providing exclusive breast milk followed by providing MP-ASI to create a quality generation (HR)